The materiality of the living dead. The carta-relación of licenciado Polo Ondegardo to archbishop Jerónimo de Loaysa of 1566 and its context - Lamana, Gonzalo (2023)
In early 1566, licenciado Polo Ondegardo, a reputed expert in Indigenous matters, sent archbishop Jerónimo de Loaysa a detailed —and until today unknown — carta-relación about native ideas and practices related to death. Polo wrote it at Loaysa´s request, a fact which requires explanation, given that he had already sent him an extensive treaty on Indigenous religions in 1559. This essay searches for answers by examining the debate on the exploitation of huacas and burials, the Taqui Onqoy, and the progressive shift from the first to the second evangelization in the Andean territory.